The Thermal Time Constant of an Electrothermal Microcantilever Resonator - Zarog, Musaab (Micro and Nanosystems, 2023)
Background: The thermal time constant is the core parameter for determining the dynamic response of the electrothermal actuators and the corresponding maximum operational frequency. Aim: Since it is necessary to determine how the thermal actuation occurs within the cantilever, this paper presents two models for the thermal time constant of bimetal microcantilevers. One model is based on the bimetallic effect, and the second is based on temperature gradients in layers. Methods: In order to investigate and check the validity of the two proposed models, the device was actuated electrothermally, and the thermal time response was estimated. A driving voltage was applied to the platinum electrode. The first model is based on the interface thermal resistance between the base and the top electrode layer. The second model assumes that the temperature gradients within the base layer are responsible for thermal actuation. Results: The microcantilever was excited electrothermally with a resonance frequency of 1.89 MHz. The bimetallic effect was found to be less able to stimulate the microcantilever at this resonance frequency. Therefore, it was concluded that thermal actuation occurred as a result of temperature variation within the SiC base layer. Conclusion: The results also indicated that temperature variations within one of the two materials in contact might be responsible for thermal actuation, especially if the material has high thermal conductivity.
Keywords: resonance frequency